유치원에서의 특별활동 실시 현황 및 교사의 인식 - 이기숙(Ki Sook Lee); 장영희(Young Hee Chang); 정미라(Mi Ra Chung); 홍용희(Yong Hee Hong) (Korean Journal of child studies, 2002)
In response to a growing trend toward downward escalation of public school curriculum, the present study surveyed so-called extracurricular activities in kindergartens and analyzed teacher's perception of these activities. Questionnaires were mailed to 1300 private kindergartens and 1116 responses were received. Major findings were that over 89% of the respondents reported doing extracurricular activities in their kindergartens, mostly using 3-4 different kinds of special activities. The 3 most highly ranked lessons in order of frequency were English, art and physical activity. Whole group time was most often used for extracurricular activities. Kindergarten teachers were concerned with the qualifications of teachers for these activities. Teachers of these extra activities usually have no specialized training or supervised experience working with 3-through 5-year-old children.